2022
DOI: 10.1002/er.8739
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the thermal properties of Al 2 O 3 ‐CuO /water hybrid nanofluids: Development of an artificial intelligence model

Abstract: Summary In this work, Al2O3 and CuO nanoparticles were synthesized by a novel sol‐gel method. Then, water‐based Al2O3 and Al2O3‐CuO (50:50) nanofluids were produced by the two‐step method. The viscosity and thermal conductivity of nanofluids were determined for the concentration and temperature range of 0‐1.0 vol.% and 30‐60°C, respectively. Sodium dodecylbenzene sulfonate surfactant was used to enhance the nanofluid stability. Field emission scanning electron microscopy, transmission electron microscopy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Inspired by the enhanced heat transfer rate and cooling performance of nanoliquids, the researchers put their efforts on the study of multiple type of nanoliquids. Recently, Gangadhar et al [ [18] , [19] , [20] , [21] ], Marulasiddeshi et al [ 22 ], Wanatasanappan et al [ 23 ], Kotha et al [ 24 ], Bhargavi et al [ 25 ], Kanti et al [ [26] , [27] , [28] ] investigated the heat transfer efficacy of multiple nanoliquids using various geometries effects and the model parameters. The authors focused on both single as well as two phase nanoliquid models.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the enhanced heat transfer rate and cooling performance of nanoliquids, the researchers put their efforts on the study of multiple type of nanoliquids. Recently, Gangadhar et al [ [18] , [19] , [20] , [21] ], Marulasiddeshi et al [ 22 ], Wanatasanappan et al [ 23 ], Kotha et al [ 24 ], Bhargavi et al [ 25 ], Kanti et al [ [26] , [27] , [28] ] investigated the heat transfer efficacy of multiple nanoliquids using various geometries effects and the model parameters. The authors focused on both single as well as two phase nanoliquid models.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles are made of metal and metal oxides [15], carbon nanotubes [16], and graphene-based nanofluids in the fields of heat transfer, [17]. Choosing the type of nanoparticle base fluids and their concentration is vital when preparing nanofluids with thermal properties that can be utilized in different heat transfer applications, [18]. The preparation methods significantly affect the thermal properties.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the thermal performance of nanofluids, many experimental studies have been carried out by researchers and their comparisons with numerical models have been made. In these studies, it was concluded that nanofluids enhancement thermal properties 15‐19 …”
Section: Introductionmentioning
confidence: 99%
“…In these studies, it was concluded that nanofluids enhancement thermal properties. [15][16][17][18][19] Hezajian et al 20 examined the effects of nanofluid use on heat transfer on a straight pipe by way of using H 2 O-Al 2 O 3 nanofluid in flow involving turbulent forced convection heat transfer. In this numerical analysis, he modelled the flow as multiphase and the methods he utilized are Mixture and Eulerian approaches.…”
Section: Introductionmentioning
confidence: 99%